Open or close the door to the outgroup? Diversity beliefs moderate the impact of group boundary permeability on attitudes toward the outgroup. (9th October 2018) - Ren, Deyun; Tan, Xuyun; Dang, Jianning; Liu, Li; Zhao, Xian; Li, Chao; Liang, Yuan; Su, Qian; Gu, Zibei; Wei, Cong
Abstract : The present research investigated the moderating role of diversity beliefs with the aim of reconciling inconsistent findings regarding the impact of group boundary permeability on attitudes toward outgroup. In Study 1, all variables were measured with self‐report scales completed by Chinese participants. In Study 2, diversity beliefs were manipulated by randomly assigning Chinese participants to a high or low diversity belief condition. In Study 3, we replicated the moderating model with American participants. Results of all three studies indicated that diversity beliefs moderated the relationship between group boundary permeability and attitudes toward outgroup. Individuals with high diversity beliefs held more positive attitudes toward the outgroup when the group boundary was permeable (vs. impermeable). Conversely, individuals with low diversity beliefs held more negative attitudes toward the outgroup when the group boundary was permeable (vs. impermeable). These findings suggest that when the inflow of the outgroup members is inevitable, attitudes toward the outgroup may be effectively improved by increasing diversity beliefs.